Temporomandibular disorders in fibromyalgia patients: are there different pain onset? - Fábio J. C. Fujarra; Helena Hideko Seguchi Kaziyama; Silvia Regina D. T. de Siqueira; Lin Tchia Yeng; Cinara M. Camparis; Manoel Jacobsen Teixeira; José Tadeu Tesseroli de Siqueira (Arquivos de Neuro-Psiquiatria, 2016)
ABSTRACT Objective To identify temporomandibular disorders (TMD) symptoms in two groups of fibromyalgia patients according to the temporal relation between the onset of facial pain (FP) and generalized body pain (GBP). Cross-sectional study design: Fifty-three consecutive women with fibromyalgia and FP were stratified according to the onset of orofacial pain: Group-A (mean age 47.30 ± 14.20 years old), onset of FP preceded GBP; Group-B (mean age 51.33 ± 11.03 years old), the FP started concomitant or after GBP. Clinical assessment Research Diagnostic Criteria for Temporomandibular Disorders and the Visual Analogue Scale. Results Myofascial pain with mouth opening limitation (p = 0.038); right disc displacement with reduction (p = 0.012) and jaw stiffness (p = 0.004) were predominant in Group A. Myofascial pain without mouth opening limitation (p = 0.038) and numbness/burning were more common in Group B. Conclusion All patients had temporomandibular joint symptoms, mainly muscle disorders. The prevalence of myofascial pain with limited mouth opening and right TMJ disc displacement with reduction were higher in Group A.